2006
DOI: 10.3758/bf03193262
|View full text |Cite
|
Sign up to set email alerts
|

Reading strategies and prior knowledge in learning from hypertext

Abstract: In two experiments, we identified two main strategies followed by hypertext readers in selecting their reading orders. The first consisted in selecting the text semantically related to the previously read section (coherence strategy), and the second in choosing the most interesting text, delaying reading of less interesting sections (interest strategy). Comprehension data revealed that these strategies affected learning differently as a function of the reader's prior knowledge. For low-knowledge readers, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
3
20

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 61 publications
6
79
3
20
Order By: Relevance
“…This result corroborates previous findings showing that prior knowledge lead readers to follow more coherent reading orders in non-linear documents [12]. However, that is not consistent with the works conducted by Salmerón and his colleagues [14,15] which showed that high prior knowledge readers benefited from low coherent reading orders. Nevertheless, we argue that those different results are compatible.…”
Section: Prior Knowledge and Hypertexts Comprehensionsupporting
confidence: 53%
See 2 more Smart Citations
“…This result corroborates previous findings showing that prior knowledge lead readers to follow more coherent reading orders in non-linear documents [12]. However, that is not consistent with the works conducted by Salmerón and his colleagues [14,15] which showed that high prior knowledge readers benefited from low coherent reading orders. Nevertheless, we argue that those different results are compatible.…”
Section: Prior Knowledge and Hypertexts Comprehensionsupporting
confidence: 53%
“…Whereas following high coherent reading orders lead low prior knowledge readers to high comprehension scores, following low coherent reading orders lead high prior knowledge to high comprehension scores [14,15]. Prior knowledge supplies resources to conduct inferences in orders to fill in coherence gaps between text sections (i.e.…”
Section: Empirical Evidences On On-line Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their reading process is very selective and is based on how much they know about the subject and what their interests are. Their reading patterns, therefore, are not as coherent as those with less prior knowledge (Salmeron, Kintsch, & Canas, 2006). Other factors identified to affect online reading comprehension include readers cognitive flexibility (Dommes et al, 2011), visual aesthetics (Norman, 2004;Tractinsky et al, 2006), computer experience (Hill et al, 2011), perceptions of website interface and media richness (Chen et al, 2011), preference of reading delivery mode (Vandelanotte et al, 2012), previous online reading experiences (Huang, 2012), contextual factors, and readers' personal characteristics (Adesope et al, 2011).…”
Section: Reading Strategies and Impact Factorsmentioning
confidence: 99%
“…A coherent reading order consists of selecting text sections that are semantically related to the one just read. In one experiment [7] found that LPK participants who selected a coherent reading order acquired higher levels of comprehension than participants who selected a less coherent reading order. Readers with more prior knowledge comprehended equally well regardless of the link selection strategy they followed.…”
Section: Introductionmentioning
confidence: 99%